VLSI-SoC : System-on-Chip in the Nanoscale Era - Design, Verification and Reliability : 24th IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2016, Tallinn, Estonia, September 26-28, 2016, Revised Selected Papers /: System-on-Chip in the Nanoscale Era - Design, Verification and Reliability : 24th IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2016, Tallinn, Estonia, September 26-28, 2016, Revised Selected Papers. (2017) - Unknown
No abstract available